Quality of ‘Valencia Delta’ orange after degreening and coating with wax - Gerlândia da S. Pereira; Francisca L. de C. Machado; José M. C. da Costa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In this study, oranges of the cultivar ‘Valencia Delta’ were degreened, coated with carnaúba-based wax and stored under refrigeration. The influence of the application of exogenous ethylene and coating was observed on physical and physico-chemical properties of the fruits. After the application of the treatments, the fruits were refrigerated (7 ± 2 oC) for a period of 35 days. The analyzed variables included weight loss, peel color, titratable acidity, ascorbic acid, total soluble sugars, reducing sugars, total polyphenols and total chlorophyll of the peel. The coated fruits showed significant reduction in weight loss when compared with the uncoated fruits, which lost about 3.0% of moisture at the end of the experiment. Significant reduction in the values of hue angle, accompanied by sharp deterioration in chlorophyll contents, suggested that the applied ethylene concentration was efficient in reducing green peel color. The contents of total polyphenols, total soluble sugars and reducing sugars increased while ascorbic acid decreased. The application of the coating, after degreening, was fundamental in maintaining the quality of the ‘Valencia Delta’ orange during storage.